O pólen em plantas da Amazônia: gêneros Poraqueiba Aubl. e Emmotum Desv. (Icacinaceae). - Carvalho, Maryan J. C. (Museu Paraense Emílio Goeldi, 2011)
The pollen morphology of three amazonian species of the genus Poraqueiba Aubl. and six of Emmotum Desv. is studied. The pollen grains are more or less uniform in the two genera. The little variation in the shape and size are not of taxonomical importance . In an europalinous family as Icacinaceae the two genera represent groups very homogeneous.